Evaluating the Combined Effects of Transverse Pitch Ratio and Flow Arrangement on the Thermo-Hydraulic Performance of a Novel Inclined Delta Winglet - Hüseyin Zahit Demirağ (Hittite Journal of Science and Engineering)

(untitled)
In this work, the in-depth examinations of the Novel Inclined Delta Winglet (NIDW) in terms of heat transfer performance and the flow characteristics are conducted at Re=5000-17500, utilizing (SST) k-ω turbulence model. In accordance with the objective of this investigation, the combined effects of the positioning of the NIDW in common-flow-down (NIDW-CFlowD) and common-flow-up (NIDW-CFlowU) orientations together with two transverse pitch ratios [Pt=0.333 and 0.166] are investigated and the resulting data are presented in a comparative manner. The angle of attack [α=30°] and the angle of inclination [β=30°] of the NIDW are kept constant. The numerical results indicate that the NIDW-CFlowD orientation at Pt=0.333 has more pronounced effect in terms of thermal performance, with an approximate increase of 4.29% increase in the Nusselt number at Re=17500, whereas the opposite trend is observed at Pt=0.166, yielding a smaller rise of around 3.13% in Nusselt number at Re=17500. The reversal in trend is entirely due to the positioning of the NIDW in the CFlowD orientation, which causes the vortex rotation centers to move further apart in the main flow direction, resulting in 4.36% and 4.02% higher Darcy friction factors in cases of Pt=0.333 and Pt=0.166, respectively compared to CFlowU configuration at Re=5000. Therefore, the highest and lowest ranges of Thermal Enhancement Factor (TEF) are calculated to be between 1.325-1.215 and 1.221-1.122 for the cases of NIDW-CFlowU with Pt=0.166 and NIDW-CFlowU with Pt=0.333 respectively. This corresponds to an increase in TEF of around 8.52%and 8.30% increase in TEF at Re=5000 and 17000, respectively.